Effects of Strain and Stocking Density on Performance, Egg Size Distribution, Egg Quality, and Welfare in Laying Hens Housed in Enriched Cage System - A Akyol; A Şekeroğlu; B Tainika; YE Şentürk; M Duman; SH Abacl; FM Gür (Brazilian Journal of Poultry Science, 2024)
ABSTRACT This study assessed the effect of strain and enriched cage stocking density on performance, egg size distribution, egg quality, and welfare status in laying hens. Lohmann brown (LB) and Lohmann LSL Classic (LW) strains at 20 weeks of age were allotted to different cage stocking densities, with 1016, 762, or 610 cm2 of cage floor area per hen. Live body weight at the age at sexual maturity and at 52 weeks of age, feather condition, and some egg quality parameters differed between hen strains and among stocking densities (p<0.01; p<0.05). However, age at sexual maturity, livability, egg production, heterophil-to-lymphocyte ratio, and duration of tonic immobility were similar between hen strains and among stocking densities (p>0.05). Furthermore, egg size distribution was similar between hen strains (p>0.05), but dissimilar among stocking densities (p<0.01). Rectal and comb temperatures differed between hen strains and among stocking densities, respectively (p<0.01; p<0.05). The age of hens influenced egg quality variables (except for egg weight and shape index), feather condition, and body region temperatures (p<0.01). These results suggest that an enriched cage floor area of up to 610 cm2 per hen does not compromise production performance and welfare status, except for the body weight of laying hens. Additionally, the two strains might be at similar levels regarding overall performance and welfare status, excluding body weight and feather condition.